Information on drugs received by out patient at North Colombo Teaching Hospital , Ragama - Karunapalan, P (My University, 2007)
Non-adherence by patients to prescribed medications has significant financial consequences. Increasing patient knowledge on drug therapy is said to improve compliance. To design and implement new interventions and to improve patients' knowledge about prescribed drugs, the amount of drug information received by patients and their socio-demographic characteristics should be known. Thereby, a descriptive profile could be developed, which would be useful to doctors and pharmacists in helping to identify patients with specific socio demographic characteristics, who need special attention when providing drug information. This descriptive cross-sectional study was carried out in November 2006 with the objective to describe the socio-demographic characteristics of patients treated at the Out Patient Department of the North Colombo Teaching Hospital. Ragama and to assess the information received by them about drugs, issued to them from the pharmacy and the source of that knowledge (including written information). This descriptive cross-sectional study was carried out in November 2006 With the objective to describe the socio-demographic characteristics of patients treated at the out Patient Department of the North Colombo Teaching Hospital, Ragama and to assess the Information received by them about drugs, issued to them from the pharmacy and the source of that knowledge ( including written information). The research showed that respondent's age had no influence on the amount of drug information known to them, Female respondents had better drug knowledge than males, Respondent's level of education had a positive influence on the amount of drug information known to them. The findings of this study calls for improvement in the provision of drug information to patients